Analisa Kegagalan pada Spindle Mesin Batch Centrifugal - Purnowidodo, Anindito; Wahjudi, Ari; Prawira, Riza (Jurnal Rekayasa Mesin, 2011)
Failure analysis was conducted on the failure shaft of batch centrifugal. In the analysis the stress analysis was used to know the stress distribution, and in conjuction with stress analysis the life time of the component can be estimated. In addition, the fractography anlaysis together with mechanical properties test were carried out to understand the mechanism of the failure. With respect to the result of analysis shows that the failure was caused by fatigue crack initated on the surface of shaft due to the inhomogeneus mechanical properties, in this case, the hardness is lower than that on sub surface of the shaft. Besides that, the stress concentration was found take place on the surface of shaft on which the crack was initated. Further, it was known that during machining process, the material of shaft was heated on elevated temperature on the surface to ease the process. The heating reduced the hardness as well as the strength of the material.Keywords : Failure, Fatigue, Crack.